Bank capital and liquidity creation: Granger-causality evidence - Roman Horváth; Jakub Seidler; Laurent Weill (European Central Bank (ECB), 2012)
We examine the relation between capital and liquidity creation. This issue is interesting because of the potential impact on liquidity creation from tighter capital requirements such as those in Basel III. We perform Granger-causality tests in a dynamic GMM panel estimator framework on an exhaustive data set of Czech banks, which mainly includes small banks from 2000 to 2010. We observe a strong expansion in liquidity creation until the financial crisis that was mainly driven by large banks. We show that capital negatively Granger-causes liquidity creation in this industry, where majority of banks are small. But we also observe that liquidity creation Granger-causes a reduction in capital. These findings support the view that Basel III can reduce liquidity creation, but also that greater liquidity creation can reduce banks' solvency. Thus, we show that this reverse causality generates a trade-off between the benefits of financial stability induced by stronger capital requirements and the benefits of increased liquidity creation.
Keywords: G21; G28; 330; bank capital; Basel III; Liquidity creation